Alpha-Gal Syndrome: Involvement of Amblyomma americanum α-D-Galactosidase and β-1,4 Galactosyltransferase Enzymes in α-Gal Metabolism - Sharma, Surendra Raj; Crispell, Gary; Mohamed, Ahmed; Cox, Cameron; Lange, Joshua; Choudhary, Shailesh; Commins, Scott P.; Karim, Shahid (Frontiers in Cellular and Infection Microbiology, 2021)
Alpha-Gal Syndrome (AGS) is an IgE-mediated delayed-type hypersensitivity reaction to the oligosaccharide galactose-α-1, 3-galactose (α-gal) injected into humans from the lone-star tick (Amblyomma americanum) bite. Indeed, α-gal is discovered in salivary glands of lone-star tick; however, the tick’s specific intrinsic factors involved in endogenous α-gal production and presentation to host during hematophagy are poorly understood. This study aimed to investigate the functional role of two tick enzymes, α-D-galactosidase (ADGal) and β-1,4 galactosyltransferases (β-1,4GalT), in endogenous α-gal production, carbohydrate metabolism, and N-glycan profile in lone-star tick. The ADGal enzyme cleaves terminal α-galactose moieties from glycoproteins and glycolipids, whereas β-1,4GalT transfers α-galactose to a β1,4 terminal linkage acceptor sugars—GlcNAc, Glc, and Xyl—in various processes of glycoconjugate synthesis. An RNA interference approach was utilized to silence ADGal and β-1,4GalT in Am. americanum to examine their function in α-gal metabolism in tick and AGS onset. Silencing of ADGal led to the significant downregulation of genes involved in galactose metabolism and transport in Am. americanum. Immunoblot and N-glycan analysis of the Am. americanum salivary glands showed a significant reduction in α-gal levels in silenced tissues. However, there was no significant difference in the level of α-gal in β-1,4GalT-silenced tick salivary glands. A basophil-activation test showed a decrease in the frequency of activated basophil by ADGal-silenced salivary glands. These results provide an insight into the roles of ADGal and β-1,4GalT in α-gal production and presentation in ticks and the probable involvement in the onset of AGS.